Estetisasi Kesedihan dalam Konten Digital: Analisis Humaniora atas Ekspresi Emosional di Era Budaya Digital - Daniel Marlasputra Simbolon; Ekananda Haryadi (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study explores the phenomenon of aestheticizing sadness in digital content as a form of emotional expression in the digital culture era. Using a qualitative approach and content analysis methods on academic literature and humanities theory, this study maps aesthetic practices in visual, narrative, and communal dimensions. The results show that digital content emphasizing sadness functions as a means of emotional communication that allows individuals to express themselves while building intense and collective social interactions. This aesthetics of sadness creates an immersive experience that strengthens online community solidarity and shapes a flexible yet consistent digital identity. These findings contribute to the understanding of digital humanities, sociology of emotions, and cultural studies by emphasizing the importance of aesthetics as a mechanism of interpretation and social interaction in the virtual world. This study recommends further research on the psychological, social, and cultural implications of the aestheticization of emotions in digital media.